Sobre ética y moral algunas precisiones útiles para estudiantes de deontología jurídica - Campos Zamora, Francisco J. (2020)
This paper does not intend to be particularly innovative. Many already seek to be so. There is no hidden secret for the uninitiated. Our purpose is much simpler, though no less relevant; this is to make the origin and evolution of the term ethics and morals as explicit as possible for those students who take their first step into the study of legal deontology, a subject that sometimes does not receive a deserved attention from law schools. Anyone speaking of origin and evolution is also speaking of the word because language is always the beginning of things. Hence this first step is rooted in the linguistic analysis of the term ethics and morals. We cannot think of any issues that can be addressed before this, if we want to conduct a serious and coherent study on deontology. Here, we will clarify the etymological background of the term morals and ethics and their modern linguistic uses as well as the conceptual contents assigned to the notions of descriptive ethics, normative ethics, and  especially metaethics.